Peran Lembaga Filantropi untuk kesejahteraan Masyarakat: (Studi Kasus pada Yayasan Gemma Insani Indonesia) - Siti Mariam; Ita Rodiah (JURNAL SOSIAL, 2024)
Philanthropy is a concrete form of generosity. At present there are many social institutions and organizations that are actively carrying out philanthropic activities. Campaigns to raise public funds, which will later be used for socio-religious and humanitarian activities, are carried out in various ways, be it through advertising in print and electronic mass media, as well as through social media. the rise of philanthropic activities aimed at encouraging and improving the standard of living of the dhu'afa in Indonesia can be motivated by various factors, it could be that the spread of philanthropic activities is a response from society to the weak role of the state in alleviating poverty, or it could be due to other factors such as awareness of faith which is getting stronger. In Islam, the concept of philanthropy is known as zakat, infaq, shadaqah (ZIS) and waqf. These terms refer to the act of giving, which implies sharing, generosity, social justice as well as mutually reinforcing human beings. The “Gemma Insani Indonesia Foundation” is one of the institutions that takes part in philanthropic activities. One of the factors behind the emergence of this institution is due to a sense of concern, as well as concern for the wider community, especially the people in West Java. This study aims to provide an overview of the Gemma Insani Foundation, along with its roles and contributions through the activity programs they carry out. The research method used is descriptive qualitative research method, by analyzing data sourced from social media accounts (Website & Instagram), literature studies as well as interviews from one of the Foundation's volunteers. The research results show that the Gemma Insani Indonesia Foundation plays an active role in efforts to improve people's welfare, with program activities carried out covering several aspects of life, including in the social, educational and entrepreneurial fields.